Spatial typology for targeted food and nutrition security interventions - Marivoet, Wim; Ulimwengu, John M.; Sedano, Fernando (Elsevier, 2019)
In this paper we develop a typology to help design and improve spatial targeting of food and nutrition security (FNS) interventions. Using a comprehensive framework, the proposed approach allows for the broad identification and location of major food security bottlenecks. The resulting typology is based on an amendable demarcation of areas in a four-indicator diagram representing the four core dimensions of FNS. The proposed typology is applied to the rural territories of the Democratic Republic of the Congo (DRC). Despite a continuum of heterogenous development challenges across the country, the typology helps identify clusters of territories that suffer from production, access, and utilization constraints. For the nine territories (out of 145) with the highest child stunting levels, we identify four broad intervention zones and analyze their efficiency profile in more detail. Despite its reductionist nature, our typology is conceptually sound, operationally flexible, and less data intensive, important features to promote evidence-based policymaking in contexts characterized by imperfect and scarce data.